Herbal Tea Production from Moringa Oleifera Leaf - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Moringa oleifera is an important medicinal plant in Vietnam. The leaf of Moringa oleifera has shown the presence of some bioactive components which possesses phytochemical activity. It is highly valued as its vast medicinal properties. Moringa oleifera is currently being promoted as a means to combat poverty and malnutrition. The phytochemical and nutritional properties of the dried leaf of Moringa oleifera used as nutraceuticals, dietary supplements, functional foods. The low moisture content of the dried leaf tea is an attribute to a very high shelf life. Long storage of the dried Moringa oleifera leaf tea would not lead to spoilage due to microbial attack and this supports the practice of storage in dry form. Objective of this study focused on the effect of blanching temperature and time; heat pump drying temperature and storage condition to vitamin C (mg/100g), flavonoid (mg/g) and sensory score of the dried Moringa oleifera leaf tea. Results showed that Moringa oleifera leaves should be blanched in hot water 95oC at 4 seconds in the present of CaCl2 2% and then beeing dried by heat pump dryer at 40oC until 6.5% moisture. The final herbal tea could be preserved under vacuum in PET/AL/PE bag at 4oC to maintain flavonoid content for 12 months. Keywords: Moringa oleifera, Herbal tea, Blanching, Drying, Vaccum, Vitamin C, Flavonoid.